2020
DOI: 10.1108/lodj-03-2020-0085
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exploitative leadership on knowledge hiding: a conservation of resources perspective

Abstract: PurposeDrawing on conservation of resources (COR) theory, this study aims to explore the influencing mechanism of exploitative leadership on knowledge hiding. Specifically, this study focuses on the mediating role of psychological distress and the moderating role of hostile attribution bias in affecting the mediation.Design/methodology/approachData were collected from 324 employees of a high-technology company in China by a three-wave questionnaire survey. Hierarchical regression analysis and bootstrapping app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 52 publications
(105 reference statements)
2
102
0
2
Order By: Relevance
“…The relationship between exploitative leadership and organizational cynicism As a kind of destructive leadership, EL constitutes a negative organizational pressure (Schmid et al, 2019;Guo et al, 2020), which denotes that EL can act as a resource-exhaustion leadership (Guo et al, 2020). EL can be described as leadership with an elementary intention to further the self-interest of leaders (Schmid et al, 2019).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between exploitative leadership and organizational cynicism As a kind of destructive leadership, EL constitutes a negative organizational pressure (Schmid et al, 2019;Guo et al, 2020), which denotes that EL can act as a resource-exhaustion leadership (Guo et al, 2020). EL can be described as leadership with an elementary intention to further the self-interest of leaders (Schmid et al, 2019).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Exploitative leaders deplete followers' valued individual resources related to self-esteem and self-respect. Besides, it is well recognized that the support of leaders is the most worthy social resource in the organization (Lee et al, 2018;Hobfoll, 2001;Guo et al, 2020).…”
Section: The Mediating Role Of Emotional Exhaustionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study (Ghiasipour, Mosadeghrad, Shaqura & Jaafaripooyan, 2020) found that employees managed with a transformational leadership style had higher levels of job satisfaction when compared to associated factors such as charisma and intellectual stimulation. Employees managed under a transactional leadership style, on the other hand, reported higher levels of job dissatisfaction when compared to associated factors such as management by exception (Luo, Guo, & Cheng, 2020). As a result, in the current climate, the role of a leader is critical to organisational success.…”
Section: Introductionmentioning
confidence: 99%